Measuring Technical Vocational Education and Training (TVET) Efficiency: Developing a Framework - John Clayton; Guimei Liu (Flexible Learning Association of New Zealand, 2016)
The growing demand for an increasingly skilled competitive workforce and the associated demand for change and responsiveness in the provision of technical vocational education and training (TVET) has led to the development of stronger links between New Zealand and the People's Republic of China. A collaborative model programme project aims to improve TVET provision in the two countries through curriculum re-design, joint programme development, and the delivery of quality New Zealand qualifications in China. Because there is there is often a gap or disconnect between policy intent and classroom reality, a critical activity of the model programme project aims to identify and measure when, how, and where this disconnect occurs. This paper identifies the performance indicators that are used to measure learner and institutional success, highlights the strategies used to evaluate the learning environments created, and reports on the development and validation of a user-driven, flexible, internet-based, learning environment instrument for use in multi-national TVET settings. It argues that this instrument provides model programme stakeholders with sufficient data to understand, economically and efficiently, the actual effect of change at the point of delivery.